Aggravation of fibrin deposition and microthrombus formation within the graft during kidney transplantation - Tamar A. J. van den Berg; Marius C. van den Heuvel; Janneke Wiersema-Buist; Jelle Adelmeijer; Gertrude J. Nieuwenhuijs-Moeke; Ton Lisman; Stephan J. L. Bakker; Harry van Goor; TransplantLines Investigators; Robert A. Pol (Scientific Reports, 2021)
Abstract In kidney transplantation, microthrombi and fibrin deposition may lead to local perfusion disorders and subsequently poor initial graft function. Microthrombi are often regarded as donor-derived. However, the incidence, time of development, and potential difference between living donor kidneys (LDK) and deceased donor kidneys(DDK), remains unclear. Two open-needle biopsies, taken at preimplantation and after reperfusion, were obtained from 17 LDK and 28 DDK transplanted between 2005 and 2008. Paraffin-embedded sections were immunohistochemically stained with anti-fibrinogen antibody. Fibrin deposition intensity in peritubular capillaries(PTC) and glomeruli was categorized as negative, weak, moderate or strong and the number of microthrombi/mm2 was quantified. Reperfusion biopsies showed more fibrin deposition (20% to 100% moderate/strong, p < 0.001) and more microthrombi/mm2 (0.97 ± 1.12 vs. 0.28 ± 0.53, p < 0.01) than preimplantation biopsies. In addition, more microthrombi/mm2 (0.38 ± 0.61 vs. 0.09 ± 0.22, p = 0.02) and stronger fibrin intensity in glomeruli (28% vs. 0%, p < 0.01) and PTC (14% vs. 0%, p = 0.02) were observed in preimplantation DDK than LDK biopsies. After reperfusion, microthrombi/mm2 were comparable (p = 0.23) for LDK (0.09 ± 0.22 to 0.76 ± 0.49, p = 0.03) and DDK (0.38 ± 0.61 to 0.90 ± 1.11, p = 0.07). Upon reperfusion, there is an aggravation of microthrombus formation and fibrin deposition within the graft. The prominent increase of microthrombi in LDK indicates that they are not merely donor-derived.